Stop staring : facial modeling and animation done right. - Osipa, Jason, ....- (Indianapolis : Wiley, 2007)
Breathe life into your creations With detailed examples, high-quality professional images, and a touch of humor, this is the fully revised and updated second edition of Jason Osipa's best-selling book on facial animation. You'll learn the basics of design, modeling, rigging, and animation-while mastering exciting new techniques for stretch-and-squash deformation, advanced blend extraction, and the latest software tools. Walk through the author's detailed analysis of sample animations and discover how to add nuance and sophistication to your designs. Full of insights drawn from years of professional experience, this book provides the focused and practical information you need to create believable facial animations. Learn visimes and lip sync techniques Construct a mouth and mouth keys Explore the process of facial landmarking Master the cartoon techniques of squash and stretch Harness the latest advanced blend extraction tools Create interfaces for your faces Understand skeletal setup, weighting, and rigging Control faces with the book's powerful rig and learn how skin moves to make various shapes and expressions Master powerful stretch-and-squash (and squoosh!) techniques Featured on the CD Fine-tune your facial animations with the techniques demonstrated on the companion CD. Content includes tutorial files, lip sync samples, models, textures, and more.
Keywords: Tekenkunst